Persistent Hyperinsulinemic Hypoglycemia of Infancy, Clinical Presentation and Treatment (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2026)
Background Persistent hyperinsulinemic hypoglycemia of infancy also known as, congenital hyperinsulinism, is a collection of disorders that lead to persistent hypoglycemia, a result of the congenital excess of insulin secretion, and is not to be mistaken with acquired forms, which include insulinoma, iatrogenic hyperinsulinemia, and dumping syndrome. It is the most likely cause of persistent hypoglycemia in the infants and neonates.Aims of the studyTo study demographic & clinical features of patients with congenital hyperinsulinism & response to treatment.Patients and methodsCase-series study was carried out on patients with congenital hyperinsulinism, who diagnosed and/or treated at Children Welfare Teaching hospital, Baghdad Medical City started on 1st of January 2013 and ended on 30th of October 2019. In this study out of 35 patients diagnosed as congenital hyperinsulinism, only 27 patients were studied ( 8 patients were excluded because of lost follow up)ResultsAll patients were full term except for one patient was preterm.All patients had mothers without diabetes mellitus except for onePatient who had mother with gestational diabetes, 17(62%) patients were male & 10(38%) patients were female.The birth weights were ranged from 3 to 5.2 kg (median 3.5 kg), with 11(40%) patients were macrosomic.The age at presentation was ranged from 1 day to 45 months (median 1 day).The age at diagnosis was ranged from 2 day to 48 months (median 2 months), 13(48%) patients were products of normal vaginal delivery, 14(52%) patients were products of caesarian section, 5(18%) patients had positive family history of affected siblings.The parent’s consanguinity was found in 22 (81%) patients.The blood glucose level during critical sample was ranged from 8 to 49 mg/dl (median 30 mg/dl).The insulin level during critical sample was ranged from 2.6 to 182 Mu/ml (median 16.5 Mu/ml)The insulin to glucose ratio was ranged from 0.06 to 9.57 (median 0.72).Nine patients were never treated with diazoxide because the drug was not available, the remaining patients (18) were treated with diazoxide, only 4 (22%) patients were diazoxide – responsive.All 27 patients were treated with octreotide, only 13(48%) patients were responded to octreotide.Thirteen (48%) patients were underwent subtotal pancreatectomy, with 1 (8%) patient, was underwent 2nd pancreatectomy.Postoperatively 1(8%) patient developed diabetes mellitus &required insulin therapy, 12(92%) patients were still hypoglycemic & required octreotide &frequent feedings to control their blood glucose level.We come to the conclusion that the congenital hyperinsulinism is rather widespread in Iraq, and it is associated with the high consanguinity.